Changes in Cardiovascular Status and Serum Electrolyte Levels During Percutaneous Nephrolithotomy - Chowdhury, Anup Roy; Hooda, Md Nurul; Islam, Md Faisal; Chowdhury, Md Moynul Hoque; Miah, Latifur Rahman; Hasan, Shahariar Md Kabir; Babul, Safiul Alam; Khan, Md Shariful Islam (Bangladesh Journal of Urology, 2020)
Background: Due to advancement of endourology, percutaneous nephrolithotomy (PCNL) is a common procedure for removal of renal stones. Intravascular absorption of normal saline during the PCNL may result in fluid overload, electrolyte imbalance and cardiovascular instability. Objective: To evaluate the changes in cardiovascular status and serum electrolyte levels in patients undergoing percutaneous nephrolithotomy. Method: Sixty adults underwent percutaneous nephrolithotomy were studied. Among them male female ratio was 13:7 and age ranging from 20-50 years. Heart rate, blood pressure and serum electrolytes were monitored before irrigation, during irrigation and post operatively. Stone size, duration of irrigation, volumes of irrigation fluid used and amount of absorption of irrigation fluid were recorded. Result: The mean heart rate, systolic and diastolic blood pressure levels were significantly higher (p<0.05) during PCNL compared to base line values. Serum sodium, potassium levels were decreased during the operation compared to the baseline levels (p < 0.005) but mean chloride concentration increased gradually compared to baseline but it was significantly higher at 120th min of irrigation and postoperatively (p<0.05). There was no significant change of serum bicarbonate concentration compared to base line value (p>0.05). The volume of irrigation fluid varied from 10000 ml to 24000 ml with mean volume 17045(±3383) ml. Total duration of irrigation varied from 30 min to 120 min. Total absorbed irrigant varied from 200-1000 ml with mean volume absorbed 526.27(±215) ml. Conclusion: In conclusion, these changes in cardiovascular status and serum electrolyte levels during percutaneous nephrolithotomy (PCNL) may be due to the invasive nature of the intervention to the kidney and the continuous irrigation of this vital organ. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.3-7